Pengaruh Profitabilitas dan Likuiditas Terhadap Struktur Modal Pada Perusahaan Retail Trade Yang Terdaftar di BEI - Alviyah Ramadani; Wayan Cipta; Ni Made Ary Widiastini (Universitas Pendidikan Ganesha, 2021)
This study aimed at examinizing the effect of: (1) The Profitability and Liquidity on Capital Structure, (2) The Profitability on Capital Structure, (3) The Liquidity on Capital Structure in Retail Trade companies listed in Indonesian Stock Exchange. The research design uses a causal and effect relationship. The subjects used in this study were Retail Trade companies has listed in Indonesian Stock Exchange. The object of this study was profitability, liquidity and capital structure. The population of Retail Trade companies listed on the Indonesia Stock Exchange is 25 companies and those who submit the reports are 22 companies. The data collected by document recording, then analyzed by multiple linear regression analysis. The results of this study showed that: (1) Profitability and Liquidity had a significant effect on the Capital Structure with a contribution, (2) Profitability had a significant negative effect to the Capital Structure, (3) Liquidity had a significant negative effect on the Capital Structure.